Analysis of Potential Bankruptcies Using the Altman Z-Score and Springate Score Methods in The Textile and Garment Sub-Sector Manufacturing Companies Listed on The Indonesian Stock Exchange (IDX) For The 2014-2019 Period - Reni Octaviani; Dudi Haryadi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to determine whether or not there are differences in predictions bankruptcy between the Altman Z-Score and the Springate Score methods in textile and garment manufacturing companies listed on the stock Exchange Indonesia (IDX) for the 2014-2019 period. In this study, the independent variable (X) is the Altman Z-Score and Springate Score, while the dependent variable (Y) is bankruptcy. Bankruptcy is a condition that occurs when an organization is no longer able to pay off its debts. This situation does not just appear in a company, but can be seen from the condition of its financial statements. Financial distress is the initial gateway to bankruptcy. Financial distress is a stage of decline in financial conditions marked by a decrease in profit or even profit negative. This study uses secondary data in the form of financial reports annual of companies in the textile and garment sub sector. This study uses purposive sampling technique in determining the sample, so that five companies can be sampled. The test used in this study is the independent sample t-test with SPSS 21. The final result of this study is that there is no difference in the result of predictions bankruptcy between the Altman Z-Score and the Springate Score methods. This happens because both methods have a high degree of accuracy.